Effect of Nd:YAG Low Level Laser Therapy on Human Gingival Fibroblasts - Andreas S. Gkogkos; Ioannis K. Karoussis; Ioannis D. Prevezanos; Kleopatra E. Marcopoulou; Kyriaki Kyriakidou; Ioannis A. Vrotsos (International Journal of Dentistry)
Aim. To evaluate the effect of Low Level Laser Therapy (LLLT) on human gingival fibroblasts in terms of proliferation and growth factors’ secretion (EGF, bFGF, and VEGF). Materials and Methods. Primary cultures of keratinized mucosa fibroblasts were irradiated by a Nd:YAG laser 1064 nm with the following energy densities: 2.6 J/cm2, 5.3 J/cm2, 7.9 J/cm2, and 15.8 J/cm2. Controls were not irradiated. Cultures were examined for cell proliferation and growth factors’ secretion after 24, 48, and 72 hours. All experimental procedures were performed in duplicate. Data were analyzed by Student’s t-test (p<0.05). Results. All laser-irradiation doses applied promoted a higher cell proliferation at 48 hours in a dose-response relationship compared to controls. This difference reached statistical significance for the cultures receiving 15.8 J/cm2 (p=0.03). Regarding EGF, all laser irradiation doses applied promoted a higher secretion at 48 hours in a reverse dose-response pattern compared to controls. This difference reached statistical significance for the cultures receiving 2.6 J/cm2 (p=0.04). EGF levels at the other time points, bFGF, and VEGF showed a random variation between the groups. Conclusion. Within the limits of this study, LLLT (Nd:YAG) may induce gingival fibroblasts’ proliferation and upregulate the secretion of EGF. Further studies are needed to confirm these results.